IT ambidexterity for business processes: the importance of balance. Issue 4 (19th June 2018) - Heckmann, Carl Simon; Maedche, Alexander
Abstract : Purpose: In highly dynamic industries, business processes require exploitation, i.e. activities that are associated with an increase in productivity through automation, standardization, integrated architectures, and the usage of existing IT resources. As a complementary capability, exploration is needed, i.e. the ability to flexibly implement new and innovative IT resources (Lee et al., 2015). The purpose of this paper is to use the concept of ambidexterity, which is researched intensively outside the domain of business processes (e.g. Gibson and Birkinshaw, 2004; Tang and Rai, 2014), to address this paradoxical trade-off within business processes. Design/methodology/approach: The paper follows a qualitative approach. A multiple case study comprising 11 interviews and additional document analysis in six organizations is conducted in the German energy sector to examine the proposed framework. Findings: This paper shows the importance of balancing exploitative and explorative business process IT (BPIT) capabilities. The process-theoretical outcome of this study is the BPIT Capability Framework that provides explanation for the interaction between exploitation and exploration. Research limitations/implications: This study contributes to the understanding of how to build ambidextrous BPIT capabilities by explaining the underlying mechanisms for feedback loops that occur in cases of imbalance. The scope of the conducted study presents a limitation and thus future research is encouraged to further validate the findings of this paper. Originality/value: By drilling down to the process level, this paper addresses the gaps that limited empirical studies have in business process management research (Recker and Mendling, 2015) and the focus on business processes that is lacking from the literature on organizational IT management (Gregory et al., 2015).